Rapid preparation of carbon‐supported ruthenium nanoparticles by magnetic induction heating for efficient hydrogen evolution reaction in both acidic and alkaline media. Issue 3 (6th May 2022) - Liu, Qiming; Lu, Bingzhang; Nichols, Forrest; Ko, Jeffrey; Mercado, Rene; Bridges, Frank; Chen, Shaowei
Abstract: Ruthenium has been hailed as a competitive alternative for platinum toward hydrogen evolution reaction (HER), a critical process in electrochemical water splitting. In this study, we successfully prepare metallic Ru nanoparticles supported on carbon paper by utilizing a novel magnetic induction heating (MIH) method. The samples are obtained within seconds, featuring a Cl‐enriched surface that is unattainable via conventional thermal annealing. The best sample within the series shows a remarkable HER activity in both acidic and alkaline media with an overpotential of only ‐23 and ‐12 mV to reach the current density of 10 mA/cm 2, highly comparable to that of the Pt/C benchmark. Theoretical studies based on density functional theory show that the excellent electrocatalytic activity is accounted by the surface metal‐Cl species that facilitate charge transfer and downshift the d‐band center. Results from this study highlight the unique advantages of MIH in rapid sample preparation, where residual anion ligands play a critical role in manipulating the electronic properties of the metal surfaces and the eventual electrocatalytic activity. Abstract : Ruthenium nanoparticles supported on carbon paper are facilely prepared by magnetic induction heating of RuCl3 within seconds, which exhibit a Cl‐enriched surface and excellent electrocatalytic activity toward hydrogen evolution reaction in both acidic and alkaline media.